2021
DOI: 10.1093/jme/tjab166
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Developmental Stage/Age, Gamma Irradiation Dose, and Temperature in Sterilization of MaleAedes aegypti(Diptera: Culicidae) in a Sterile Insect Technique Program

Abstract: The sterilization process using gamma irradiation is a crucial component in a program using sterile insect technique (SIT) to control Aedes aegypti. Unfortunately, there is no efficient standard protocol for sterilizing mosquitoes that can produce a high level of sterility while maintaining mating ability and longevity. Therefore, we conducted a study of the critical factors necessary to develop such a standard protocol. In this study, male Ae. aegypti pupae, as well as adults aged 1 d and 3 d, were irradiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…The data presented in Table 2 show that the mean doses measured on 23/11/2021 by the MTS-N and Li2B4O7:Cu,Ag dosimeters showed percentage differences of 5.4% and 5.5%, respectively, in relation to the nominal dose. Similar results were reported by Ernawan and colleagues [10] who is a study to devise a standard protocol for sterilizing Aedes aegypti mosquitoes using a dosimetry system based on Gafchromic HD-V2 films (Ashland, Bridgewater, NJ) to confirm and verify the dose absorbed by the insects. The authors reported that the measured doses were within 5% of the dose specified by the respective irradiator setting.…”
Section: Part Of the Holdersupporting
confidence: 83%
See 1 more Smart Citation
“…The data presented in Table 2 show that the mean doses measured on 23/11/2021 by the MTS-N and Li2B4O7:Cu,Ag dosimeters showed percentage differences of 5.4% and 5.5%, respectively, in relation to the nominal dose. Similar results were reported by Ernawan and colleagues [10] who is a study to devise a standard protocol for sterilizing Aedes aegypti mosquitoes using a dosimetry system based on Gafchromic HD-V2 films (Ashland, Bridgewater, NJ) to confirm and verify the dose absorbed by the insects. The authors reported that the measured doses were within 5% of the dose specified by the respective irradiator setting.…”
Section: Part Of the Holdersupporting
confidence: 83%
“…But to read alanine dosimeters, Electron Paramagnetic Resonance (EPR) equipment is needed, which is expensive and rarely available in facilities that perform the SIT technique. For this reason, routinely Gafchromic® film systems [8] are used, due to their low-cost and simple measurement technique [2,9,10,11]. However, the performance of this dosimetric system is affected by environmental factors, such as temperature and analysis time [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been reported that lower temperatures decreased the induced sterility of Ae. aegypti irradiated at the pupal or adult stages ( Ernawan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…While efforts are still being devoted to overcome these difficulties, the focus is now shifting to irradiation during the adult stage. It has been reported that adult Aedes mosquitoes are similarly or slightly more radiosensitive than old pupae with a better quality after irradiation in some cases ( Du et al, 2019 ; Ernawan et al, 2022 ). However, the main challenge is the immobilization and compaction of a large number of adult males for homogenous irradiation with minimal deleterious effects on their downstream quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation